Things that go through your mind when falling : the work of Forced Entertainment - Heathfield, Adrian; Glendinning, Hugo (Spector Books, 2023)
"Making performance works for four decades, British experimental theatre collective Forced Entertainment has become globally renowned for its singular aesthetic and audacious events, melding narrative fragments with strange acts, broken poetry, audience provocations, and comical failure. With its low-fi theatre, intimate text-based works, and epic durational spectacles, the group has profoundly influenced the international performance scene, evoking and testing the politics of contemporary life. 'Things That Go Through Your Mind When Falling' is the definitive book on a remarkable oeuvre: an exquisite anthology of previously unseen images by photographer Hugo Glendenning, collecting interview reflections and documentary materials alongside original texts and critical essays, which make a forceful intervention in the discourse on contemporary performance." --back cover